Length of hospital stay after hip fracture and risk of early mortality after discharge in New York state: retrospective cohort study. (10th December 2015) - Nikkel, Lucas E; Kates, Stephen L; Schreck, Michael; Maceroli, Michael; Mahmood, Bilal; Elfar, John C
Abstract : Study question Can the length of hospital stay for hip fracture affect a patient's risk of death 30 days after discharge? Methods In a retrospective cohort study, population based registry data from the New York Statewide Planning and Research Cooperative System (SPARCS) were used to investigate 188 208 patients admitted to hospital for hip fracture in New York state from 2000 to 2011. Patients were aged 50 years and older, and received surgical or non-surgical treatment. The main outcome measure was the mortality rate at 30 days after hospital discharge. Study answer and limitations Hospital stays of 11-14 days for hip fracture were associated with a 32% increased odds of death 30 days after discharge, compared with stays lasting one to five days (odds ratio 1.32 (95% confidence interval 1.19 to 1.47)). These odds increased to 103% for stays longer than 14 days (2.03 (1.84 to 2.24)). Other risk factors associated with early mortality included discharge to a hospice facility, older age, metastatic disease, and non-surgical management. The 30 day mortality rate after discharge was 4.5% for surgically treated patients and 10.7% for non-surgically treated patients. These findings might not be generalizable to populations in other US states or in other countries. The administrative claims data used could have been incomplete or include inaccurate coding of diagnoses and comorbid conditions. The database also did not include patient socioeconomic status, which could affect access to care to a greater extent in New York state than in European countries. Specific cause of death was not available because few autopsies are performed in this population. What this study adds By contrast with recent findings in Sweden, decreased length of hospital stay for hip fracture was associated with reduced rates of early mortality in a US cohort in New York state. This could reflect critical system differences in the treatment of hip fractures between Europe and the USA. Funding, competing interests, data sharing University of Rochester grant from the Clinical Translational Science Institute for statistical analyses used in this work (National Institutes of Health (UL1 TR000042)) and the National Institutes of Health (K-08 AR060164-01A). No competing interests declared. Data may be obtained through SPARCS at https://www.health.ny.gov/statistics/sparcs/access/ .